From an ethnography of the everyday to writing echoes of suffering (Medicine Anthropology Theory, 2020)
Veena Das has introduced a major shift in our contemporary conception of ethnography. While she brings forward a new way of looking at everyday life, which is already a major achievement, she also offers a conceptual resolution to a classical unresolved opposition between the individual and the collective, and between idiosyncratic psychology (subjectivity) and collective modes of thinking, through a challenging debate on what makes one a member of a group and yet radically distinct from all others. The ethnography in her book Affliction stands on three major pillars: The first is the ethnographer’s subjective position in the field regarding the issues of lives, testimony, and research. The second is the neighborhood as the site of fieldwork, with all of its heterogeneity, rather than the group, such as an ethnic or racial group or one cohering around another criterion of belonging. The third and final pillar is the focus on the ordinary through ethnography of the everyday. I then illustrate Veena Das’s perspective on subjectivity with my own fieldwork with survivors of the Cambodian genocide.